Functional Analyses of Lupulin Gland-Specific Regulatory Factors from WD40, bHLH and Myb Families of Hop (Humulus lupulus L.) show Formation of Crucial Complexes Activating chs_H1 Genes - Matoušek, Jaroslav; Josef Patzak, Josef Patzak; Tomáš Kocábek, Tomáš Kocábek; Füssy, Zoltán; Stehlík, Jan; Orctová, L.; Duraisamy, Ganesh Selvaraj (BrewingScience, 2011)
Complex lupulin gland-specific cDNA library from Osvald’s clone 72 hop was constructed to dissect regulation of biosynthetic pathway(s) leading to the accumulation of hop bitter acids and prenylflavonoids with promising health-beneficial activities. From this cDNA library we isolated first hop-specific allelic isoforms of transcription factors (TF) bHLH (HlbHLH2, GeneBank AC:FR751553) and WD40 (HlWD40_1, AC:NM_122360) which are involved in combinatorial control of light-responsive and tissue-specific activation of phenylpropanoid pathway. HlbHLH2 and HlWD40_1 are quite lupulin gland-specific and, according to our transient expression experiments, they form specific complexes with another novel hop TF HlMyb2 (AC:FN646081) and previously isolated lupulin gland-specific HlMyb3 (AC:AM501509). The complex formation leads to strong activation of chalconsynthase gene (chs_H1) promoter. The interplay and regulation of expression of these crucial TF complexes could co-determine the rate of accumulation of valuable metabolites of lupulin.